Clinical profile and epidemiology of gastric cancer patients - Jeniz Saltin S; Arumugam V (Asian Journal of Medical Sciences)
Background: Gastric cancer remains a major global health concern, contributing significantly to cancer-related mortality. Its burden is particularly high in Asia, including India.